METASOMATIC HALO OF THE SAF'YANOVSKOE ZN-CU MASSIVE SULFIDE DEPOSIT, CENTRAL URALS - Grabezhev A.I.; Moloshag V.P.; Murzin V.V.; Sotnikov V.I.; Korovko A.V.; Zhukhlistov A.P. (My University, 2001)
By the example of the low-grade metamorphic (no higher than the zeolite facies) Early Devonian Saf'yanovskoe deposit in the eastern slope of the Central Urals, the complex and prolonged history of metasomatic halo formation in an ancient massive sulfide system is demonstrated. The primary metasomatic zoning of the halo under massive sulfide ores is represented by a large body of chlorite-quartz metasomatic rocks (with high-grade chalcopyrite stringer and dissemination mineralization) in the central part of the deposit, which change along dip and strike into chlorite-hydrosericite-quartz rocks. The metasomatic alteration is medium-temperature (up to 350°C, illite 2M1) in the central zone (feed channel) and changes gradually to low-temperature away from it (250°C and lower): the metasomatic rocks contain hydrosericite t-1M and then I/S-hydrosericite c-1M (electron diffraction data) in association with kaolinite. The fluid was characterized by an intermediate composition between those of magma-derived fluid and seawater (δ18 OH2O = +3.2‰ and δD = -47‰ at T = 250°C) and low carbon dioxide activity. Low-temperature hydrothermal activity continued after the burial of the massive sulfide body, which is recorded in the extensive development of sulfide-free kaolinite (dickite)-ankerite-I/S-quartz association above the massive sulfide zone. Mica hydration and carbonatization of metasomatic rocks below the massive sulfide zone were related to this stage of mineral formation. The temperature of this process was 132-197°C at a pressure of 0.30-0.37 kbar. The fluid was strongly enriched in carbon dioxide, and the isotope signature of carbonate (δ13C from -1.32 to -2.84‰ and δ18O from +18.8 to +22.2‰) suggests that the fluid actively extracted carbon dioxide from the marble framework of the deposit. During metasomatic alterations, Al and Ti behave as immobile components and the geometric volume was constant or increased on the expense of stringer and segregation silicification and sulfidization. In all cases, considerable addition of Si, Mg, and Fe and leaching of Na and Ca took place. The extensive development of chlorite-quartz metasomatic rocks in the Saf'yanovskoe deposit is not typical of the Uralian-type massive sulfide occurrences and is similar to the deposits of the Noranda region in Canada.
Keywords: low-grade metamorphic; Devonian; Saf'yanovskoe deposit; Central Urals; Paleozoic::Devonian; Палеозой::Девонская